Independent Evolution of the MYB Family in Brown Algae - Zeng, Qiangcheng; Liu, Hanyu; Chu, Xiaonan; Niu, Yonggang; Wang, Caili; Markov, Gabriel V.; Teng, Linhong (Frontiers in Genetics, 2022)
Myeloblastosis (MYB) proteins represent one of the largest families of eukaryotic transcription factors and regulate important processes in growth and development. Studies on MYBs have mainly focused on animals and plants; however, comprehensive analysis across other supergroups such as SAR (stramenopiles, alveolates, and rhizarians) is lacking. This study characterized the structure, evolution, and expression of MYBs in four brown algae, which comprise the biggest multicellular lineage of SAR. Subfamily 1R-MYB comprised heterogeneous proteins, with fewer conserved motifs found outside the MYB domain. Unlike the SHAQKY subgroup of plant 1R-MYB, THAQKY comprised the largest subgroup of brown algal 1R-MYBs. Unlike the expansion of 2R-MYBs in plants, brown algae harbored more 3R-MYBs than 2R-MYBs. At least ten 2R-MYBs, fifteen 3R-MYBs, and one 6R-MYB orthologs existed in the common ancestor of brown algae. Phylogenetic analysis showed that brown algal MYBs had ancient origins and a diverged evolution. They showed strong affinity with stramenopile species, while not with red algae, green algae, or animals, suggesting that brown algal MYBs did not come from the secondary endosymbiosis of red and green plastids. Sequence comparison among all repeats of the three types of MYB subfamilies revealed that the repeat of 1R-MYBs showed higher sequence identity with the R3 of 2R-MYBs and 3R-MYBs, which supports the idea that 1R-MYB was derived from loss of the first and second repeats of the ancestor MYB. Compared with other species of SAR, brown algal MYB proteins exhibited a higher proportion of intrinsic disordered regions, which might contribute to multicellular evolution. Expression analysis showed that many MYB genes are responsive to different stress conditions and developmental stages. The evolution and expression analyses provided a comprehensive analysis of the phylogeny and functions of MYBs in brown algae.